A Model of Service Marketing in Port Services: Empirical Study in PT Pelabuhan Indonesia II (Persero), Tanjung Priok Branch - Srihadi, Rati Farini; Hartoyo, Hartoyo; Sukandar, Dadang; Maulana, Agus (UI Scholars Hub, 2021)
Port of Tanjung Priok is one of the ports in Indonesia which has the potential to be developed into an international seaport with the level of activity and the capacity of loading and unloading. This study aims to understand the key variables that determine the service quality of the port, so as to achieve customer satisfaction and loyalty. By using Structural Equation Modeling, this study analyzes the effects of various dimensions of service quality to customer satisfaction, and the relationships formed between perceived value and customer loyalty of the port service industry in Indonesia. The sampling method used was stratified random sampling with a total of 406 respondents. The results show positive relationships between the variables. This implies that service quality is an important aspect to focus on in order for Port of Tanjung Priok to achieve customer satisfaction and loyalty.